Four Mergers: Applied AI, Blockchain Tech, Airports, and Airlines - Hamzaee, Reza G (Archives of Business Research, 2025)
Airline sustainability, airport efficiency, passengers’ net gain and social optimality would be a matter of a great incorporation of human technical and intellectual talents towards an all winning economic and financial arrangement. That cannot be easily imagined without a system of law and order and a successful implementation of ethical and moral principles and culture. The author has analyzed the efficiency of blockchain technology, AI, and airport-airlines integration, each in separate published studies. In this study, the theoretical focus is on the four essential players – airlines, airports, AI, and blockchain technology for optimization of collective social gain through internalization of the existing externalities among airlines, airports, and passengers. This would best be implemented via an interactive financial strategy, in which airports and airlines would be independently run, but commonly owned, as in a holding-company concept. The stakeholders, airports, airlines, and passengers of all kinds could reduce their costs and optimize their net gains. Through lower airfare, airlines can serve more passengers, who would use more of the two-tier airports’ landside and airside services. All that can be effectively operationalized through the advantageous integrated application of AI and blockchain technology within the merged airlines and airports, say, Airportlines. Using this proposed model, one may apply stepwise regression along with linear programming procedures, to explore optimal airport fees and allocation of resources through a collective cost minimization and/or revenue maximization, including those of airlines, airports, and the general customers, through some mandatorily established optimal government regulations.